ANALISIS SOSIOLOGI SASTRA DALAM NOVEL ATHIRAH KARYA ALBERTHIENE ENDAH - Sri Juniati; Andi Muhammad Yahya (STKIP Paris Barantai, 2018)
ABSTRACTÂ The background of this research is the role of sociology and the cultivation of social values in Athirah's novel by Alberthiene Endah. Sociology is a science that studies about the ins and outs of society, in sociology there are values that pertain to the relation ship between individuals and society. These common values are often referred to as social values. Social values not only exist in real life in society but, there is also in a literary work whose social value can be compared or linked with real life in social society. Social values are attitudes and feelings that are widely accepted by society and are the basis for formulating what which is true and what is important. Based on the background that has been described above, the purpose of this study are (1) Describe how the role of sociology in the novel Athirah works Alberthiene Endah. (2) Describe how social values are grown in Athirah's novel by Alberthiene Endah.The method used in this research is qualitative research methods that are descriptive and type of Study Pustaka (libary research) by way of mengambill object directly from the novel Athirah by Alberthiene Endah. Sources of data used in research in this study is by reading the novel carefully, while the data collection using documentation method, data analysis using content analysis. In this case the author will reveal how the role of sociology and the implantation of social values contained in the novel.The results of this study indicate that the role of sociology and social values depicted in the life story of the novel. This is known from the results of the analysis of literary sociology in the novel Athirah by Alberthiene Endah. The social values contained in Alberthiene Endah's Athirah novel are: The dominant social values, the ingrained social values, the material value, the vital value, the spiritual value, the value of beauty, Moral values, truth and empirical value, economic value.Kata kunci: Sosiologi, Sastra, Novel.